Developing Civics Education Textbook Based on ICT-Integrated Anti-Corruption Education - Widodo, Slamet; Yulianti, Yuni (Universitas Pendidikan Indonesia, 2022)
In the campus nowdays there is no special subject for anticorruption. Wereas anticorruption subject is much needed by students due to with it students can play a role actively for campaign anticorruption. The thing can be done and enable appropriate with those conditions is to integrate civics educations subject to anticorruption. During the Covid-19, the trend using technology on all aspect of life increase. Therefore, so that students have integrity character so needed civics education textbook based anticorruption education integrated ICT (information, communication, dan technology). This research aim to describe validity and practicality civics education textbook based anticorruption integrated ICT. The kind of research is needed RnD (Research and Development) with 4D Model approach (define, design, develop, and disseminate). Reserch respondent use teacher candidate student consist of 5 majors. Data collection technique use expert validation, interview, and students responses. Data are analyzed quantitatively and qualitatively. The result of validation showed that textbook declared valid with contents 8 chapters and integrated to anticorruption comprehensive. Book material is wrotten structured accurated and deep. Language is used also easy understood with diction varied and interactive. Content of textbook equipped with pictures, chart, and illustration wich could facilitate several of students learning style. The result of testing also showed that textbook practical used in the learning. Students can easy to understand and think in line to essensial material in the textbook. Moreover, textbook also easy brougth, read, and saved.